2014
DOI: 10.4025/actascibiolsci.v36i4.18373
|View full text |Cite
|
Sign up to set email alerts
|

<b>Copper sulfate acute ecotoxicity and environmental risk for tropical fish

Abstract: ABSTRACT. The aim of this study was to estimate copper sulfate acute toxicity and to determine death percentage and environmental risk on guppy fish (Phallocerus caudimaculatus), zebrafish (Brachydanio rerio), mato grosso (Hyphessobrycon eques), and pacu (Piaractus mesopotamicus). Fish were exposed to 0.01, 0.03, 0.05, 0.07, 0.10, and 0.30 mg L (pacu). Copper sulfate was extremely toxic for guppy, highly toxic for zebrafish and mato grosso and lightly toxic for pacu and presents environmental risk of high adve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 20 publications
(9 reference statements)
1
13
0
Order By: Relevance
“…In agreement with previous studies [ 32 , 33 ], we found that adult zebrafishes were more sensitive to copper than embryos. It should be emphasized that the fish development stage can significantly affect the response to copper, in line with other similar studies [ 31 , 32 , 33 ].…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…In agreement with previous studies [ 32 , 33 ], we found that adult zebrafishes were more sensitive to copper than embryos. It should be emphasized that the fish development stage can significantly affect the response to copper, in line with other similar studies [ 31 , 32 , 33 ].…”
Section: Resultssupporting
confidence: 88%
“… *—Data are presented based on the copper concentration; in brackets for HKUST-1. ** literature data [ 31 , 32 ]. …”
Section: Figures Scheme and Tablementioning
confidence: 99%
“…[46] CuCl 2 .3Cu(OH) 2 and Cu(OH) 2 were less toxic than copper sulfate to Labeo rohita (LC50;96 h D 3.15 mg L ¡1 ); [47] P. caudimaculatus (LC50;96 h D 0.05 mg L ¡1 ), B. rerio (LC50;96 h D 0.13 mg L ¡1 ) and H. eques (LC50;96 h D 0.16 mg L ¡1 ). [19] The association DC0.1%CuCl 2 .3Cu(OH) 2 was more toxic to L. minor (LC50;7 d < 0.01 mg L ¡1 ) and less toxic to H. eques (LC50;48 h D 18.97 mg L ¡1 ; 25.87-13.91 mg L ¡1 ). The bioindicators sensitivity to this association was as follows: L. minor > A. caroliniana > P. canaliculata > H. eques ( Table 1).…”
Section: Control Efficacy For the Unicellular Algae Ankistrodesmus Grmentioning
confidence: 94%
“…[18] Organisms from several levels of the food chain are used in the ecotoxicological evaluation, accordingly to features such as sensitivity, management complexity, reproductive cycle duration, geographical distribution, and size. Among some of the bioindicators used in the ecotoxicological assessments are the fish, [19] the snail [20] and aquatic macrophytes. [21,22] Thus, the aim of this research was to evaluate the efficacy of diquat, copper oxychloride and copper hydroxide (Cu(OH) 2 ), and the associations of the herbicide with 0.1% of copper oxychloride and 0.1% of copper hydroxide in the control of the unicellular algae Ankistrodesmus gracilis and the filamentous algae Pithophora kewesis, and to estimate the 50% acute toxicity (LC50) for Hypressobrycon eques, Pomacea canaliculata, Lemna minor and Azolla caroliniana.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the treated reactors declined significantly in a trend proportional to dose, the algaecide treatment might have impacted other members of the photosynthetic community. The impact of algaecide on non-target species is a largely understudied topic; however, eco-toxicological impact from copper sulfate has been well documented [6,20,22,29]. Reactors treated with half and quarter dose EarthTec depicted a rebound in chl-a of 254% (p < 0.05) and 544% (p < 0.05), respectively, from 7 to 14 days (Fig.…”
Section: Bench-scale Results Of Cyanobacteria Suppression With Earthtecmentioning
confidence: 99%